Titanium silicalite molecular sieve TS-1 nanosheet as well as preparation method and application thereof
The preparation of titanium silicon molecular sieve TS-1 nanosheets by urea-assisted synthesis method has solved the problem of low utilization rate of active centers in the catalytic cyclohexanone oximetization reaction of traditional titanium silicon molecular sieve TS-1, and achieved efficient and low-cost catalytic effect.
Patent Information
- Application Number
- CN202510272349.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
When the existing titanium silicon molecular sieve TS-1 catalyzed cyclohexanone oximetization reaction, the pore size is similar to that of the reactant molecules, resulting in low utilization rate of the active center, which limits the further improvement of the reaction activity to problems such as high cost and easy structure collapse.
Urea-assisted synthesis method was used to prepare titanium silicon molecular sieve TS-1 nanosheets by controlling the crystal growth direction, avoiding structural collapse caused by calcination and reducing synthesis cost.
The low-cost synthesis of TS-1 nanosheets of titanium silicon molecular sieve is achieved, which improves catalytic activity and reaction efficiency, avoids the problem of structural collapse, and reduces production costs.
Smart Images

Figure CN119774627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of molecular sieves, in particular to titanium silicon molecular sieve TS-1 nanosheets and a preparation method and application thereof. Background Art
[0002] Cyclohexanone oxime is often used as an intermediate for pesticides and insecticides, a stabilizer in rubber and plastic processing aids, and an important industrial raw material. It is mainly used as an intermediate for nylon-6; nylon-6, also known as polyamide-6, is an engineering thermoplastic. It is widely used in daily life, for example, it can be made into fibers, clothing, textiles, tires or cord fabrics.
[0003] Traditional cyclohexanone ammoximation is mainly divided into the Raschig process, the hydroxylamine phosphate process and the NO reduction process. The Raschig process, also known as the hydroxylamine sulfate process, uses highly corrosive fuming sulfuric acid, and the generated product contains ammonium sulfate, which is a fertilizer with extremely low practical value; the reactants and products of this method will not only corrode the process equipment, causing increased costs, but also pollute the environment, which is not in line with the concept of green ecological development. The hydroxylamine phosphate process is very cumbersome, requires a lot of equipment, and the entire process requires continuous use of H3PO4 to maintain the pH value of the entire process at 1.8~2.0. The reaction conditions are harsh, and the reaction uses expensive Pd catalysts. The NO reduction process is complicated, and the use and generation of H2SO4 are corrosive to the equipment.
[0004] In 1988, EniChem SpA of Italy developed a liquid phase ammoximation method for cyclohexanone oxime. Specifically: The liquid phase ammoximation of cyclohexanone oxime is a method in which cyclohexanone reacts with aqueous ammonia under the catalysis of titanium silicalite TS-1 and with H2O2 as an oxidant. The high activity of titanium silicalite TS-1 is attributed to its ability to form Ti(IV)-peroxide groups with strong oxidizing properties on the titanium skeleton after contact with hydrogen peroxide, thereby catalyzing the liquid phase ammoximation of cyclohexanone oxime. The method is simple and can be completed in one step. The reaction temperature is 60℃~80℃, the conditions are mild, the product is water, it is green and pollution-free, and the conversion rate, selectivity, yield and atomic utilization are all high, which meets the requirements of industrialization. Therefore, it has attracted much attention and has been industrialized.
[0005] The research of existing technologies mainly focuses on the modification of traditional titanium silicalite TS-1 to obtain higher cyclohexanone conversion rate and cyclohexanone oxime selectivity. The pores of traditional titanium silicalite TS-1 are microporous, and the active titanium species are mainly located in the pores. The diameter of cyclohexanone molecules is similar to the diameter of the pores of titanium silicalite TS-1, which will seriously hinder the diffusion of macromolecular reactants and products in the pores, resulting in low utilization of active centers, limiting further improvement of reaction activity. Existing methods for solving the problem of cyclohexanone diffusion in traditional titanium silicalite TS-1 include: synthesizing mesoporous or multi-level porous titanium silicalite TS-1, or treating titanium silicalite TS-1 after synthesis to form hollow titanium silicalite TS-1, or synthesizing nanostructured titanium silicalite TS-1.
[0006] Mesoporous or multi-level porous titanium silicalite TS-1 is mainly synthesized by the hard / soft template method. The hard / soft template method is to introduce hard / soft templates into the titanium silicalite TS-1 synthetic gel and then crystallize it. The hard template is usually a relatively rigid solid material, such as nanocarbon materials and CaCO3. The hard template is introduced into the synthetic gel to make the titanium silicalite TS-1 crystallize and grow around it, and finally obtain the mesoporous titanium silicalite TS-1. Its mesoporous characteristics are determined by the morphology and size of the hard template itself, but the removal conditions of the hard template are often harsh. Therefore, in the process of removing the hard template, the structure of the titanium silicalite is often damaged to a certain extent. At the same time, the hard template is expensive and the synthesis cost is high, which is not conducive to industrial application. Soft templates are substances that can dissolve in titanium-silicon gel and have strong interactions with all components therein, such as gelatin, cationic polymer polydiene or triblock copolymer. The addition of soft templates can construct rich and uniform mesopores inside the titanium silicate TS-1 crystal. The mesopore size can be adjusted by using soft templates of different molecular sizes. However, the soft template is in a competitive relationship with the microporous structure directing agent tetrapropylammonium hydroxide during crystallization. Its addition will make the crystallization process of titanium silicate TS-1 difficult to control and cause phase separation. In addition, the introduction of soft templates will also affect the effective crystallization of Ti, thereby entering the titanium silicate framework and causing the formation of anatase.
[0007] Introducing a hollow structure into the zeolite and forming a hollow-structured titanium silicalite TS-1 provides an alternative strategy to minimize diffusion barriers and potentially enhance the distribution of active sites during preparation. Desiliconization is the most common method to produce intracrystalline hollow structures in MFI-type zeolites, which is to place the prepared traditional titanium silicalite TS-1 together with tetrapropylammonium hydroxide in a hydrothermal reactor for secondary hydrothermal rearrangement. However, the tetrapropylammonium hydroxide used in this method is expensive, and filtering, washing, drying and calcination operations are still required after the secondary hydrothermal reaction, which greatly increases the synthesis cost.
[0008] In the preparation of nanostructured zeolites, great success has been achieved in the selective control of the morphology of nanoparticles, nanoneedles and nanosheet zeolites. Nanostructured zeolites have attracted widespread attention because their size in one or some dimensions is drastically reduced, which shortens the diffusion path of macromolecular substances and has a rapid mass transfer effect. Zeolite nanoparticles have a small particle size, which is conducive to the diffusion of substrates in catalytic oxidation reactions. However, the too small size of nanocrystals makes it difficult to separate them from synthetic mixtures and reaction systems. Particles that are too small cannot be separated by filtration and can only be obtained by expensive centrifugation. The morphology of zeolite nanoneedles is slender needle-like and very hard. It can even penetrate the skin, causing physical injuries to workers or experimental accidents. Therefore, zeolite nanosheets have attracted much attention due to their good diffusivity, easy separation and greater safety for health.
[0009] Two-dimensional layered titanium silicalite TS-1 refers to titanium silicalite TS-1 that grows regularly in two directions during the growth process, while limiting growth in the third direction. Two-dimensional layered zeolites contain several microporous crystalline sheets, each of which has a thickness of one unit. The atoms in the zeolite layer are connected by strong covalent bonds, and the adjacent zeolite layers interact through van der Waals forces, hydrogen bonds or ionic bonds, that is, the interaction between the terminal silanol groups and the charged structure directing agents, which shortens the diffusion path and improves the accessibility of the active sites. Therefore, the zeolite nanosheets have excellent mass transfer performance. In recent years, researchers have developed many methods for the synthesis of lamellar titanium silicalite TS-1, and applied titanium silicalite TS-1 to the preparation of macromolecular reactants such as olefin epoxidation. However, most methods for synthesizing titanium silicalite TS-1 nanosheets use [C6H 13 -N + (CH3)2-C6H 12 -N + (CH3)2-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -N + (CH3)2-C6H 12 -N + (CH3)2-C6H 13 ][OH - ]4 is a long-chain surfactant. This long-chain surfactant is expensive and the synthesis steps are very complicated, which limits the industrial application of sheet-like titanium silicate molecular sieves. In addition, in the process of preparing titanium silicate molecular sieve TS-1 nanosheets, it is necessary to calcine at 550℃ for 6h to remove the structural directing agent between the titanium silicate molecular sieve TS-1 nanosheets. However, due to the lack of support between the titanium silicate molecular sieve TS-1 nanosheets, the space between the titanium silicate molecular sieve TS-1 nanosheets is greatly reduced, and even the structure collapses. Summary of the invention
[0010] In view of the deficiencies in the above-mentioned prior art, the purpose of the present invention is to provide titanium silicon molecular sieve TS-1 nanosheets and a preparation method and application thereof. The present invention uses tetrapropylammonium hydroxide, tetraethyl orthosilicate, tetrabutyl titanate and urea as raw materials, first crystallizes, and then calcines to prepare titanium silicon molecular sieve TS-1 nanosheets. The present invention uses a urea-assisted synthesis method, and urea can spontaneously disperse on the surface of the crystal perpendicular to the b-axis, inhibiting the growth of the crystal along the b-axis, and then forming a sheet of titanium silicon molecular sieve TS-1 after calcination. The present invention does not need to use isopropanol as a solvent and a regulator for the hydrolysis of tetraethyl orthosilicate and tetrabutyl titanate, so as to achieve the purpose of synthesizing titanium silicon molecular sieve TS-1 nanosheets at a low cost, and overcome the technical defects of the prior art that calcination leads to structural collapse.
[0011] In order to solve the above technical problems, the present invention adopts the following technical solutions: The present invention provides a method for preparing titanium silicon molecular sieve TS-1 nanosheets, comprising the following steps: The tetrapropylammonium hydroxide solution is mixed evenly with water, and then tetraethyl orthosilicate is added and mixed evenly, and then urea is added to obtain a mixed solution, and the mass percentage of the tetrapropylammonium hydroxide solution is 25wt%; compared with the prior art titanium silicalite TS-1 preparation method, the present invention applies urea to the preparation process of titanium silicalite TS-1 to obtain titanium silicalite TS-1 nanosheets.
[0012] Tetrabutyl titanate was added dropwise to the mixed solution and stirred until it became clear to obtain a pretreatment solution.
[0013] The pretreated solution is crystallized to obtain crystals; during the crystallization process, urea is spontaneously dispersed on the surface of the crystal perpendicular to the b-axis, thereby inhibiting the growth of the crystal along the b-axis.
[0014] The crystals are washed with water until neutral, and then calcined to obtain titanium silicalite TS-1 nanosheets.
[0015] Among them, the molar ratio of tetraethyl orthosilicate to urea is 1:0.3~0.66. Urea is the main reason for the formation of titanium silicon molecular sieve TS-1 nanosheets. If it is too little, it cannot form a sheet-like morphology, and if it is too much, it cannot further change the morphology, resulting in waste; moreover, the amount of urea exceeding this range will affect the catalytic effect of titanium silicon molecular sieve TS-1 nanosheets.
[0016] Preferably, the molar ratio of tetraethyl orthosilicate:tetrabutyl titanate:tetrapropylammonium hydroxide is 1:0.008-0.06:0.125-0.35.
[0017] Preferably, the crystallization method is: heating at 110° C. to 170° C. for 24 h to 80 h.
[0018] Preferably, the calcination conditions are: calcination at 550°C for 5h~7h. If the calcination temperature is too low, the tetrapropylammonium hydroxide, organic matter and urea inside the titanium silicon molecular sieve TS-1 nanosheet cannot be effectively removed. The organic matter is the decomposition of tetraethyl orthosilicate and tetrabutyl titanate during the crystallization process; if the calcination temperature is too high, it will affect the structure of the titanium silicon molecular sieve TS-1 nanosheet and cause the structure to collapse. In addition, calcination at 550°C is mainly to remove tetrapropylammonium hydroxide and organic matter inside the pores of the titanium silicon molecular sieve TS-1 nanosheet, and urea is removed accordingly.
[0019] Preferably, tetrabutyl titanate can also be first dissolved in isopropanol to obtain a tetrabutyl titanate solution, and then the tetrabutyl titanate solution is added to the mixed solution. The present invention can directly add tetrabutyl titanate to the mixed solution without isopropanol as a solvent for tetrabutyl titanate.
[0020] The invention also protects the titanium silicon molecular sieve TS-1 nanosheets prepared by the preparation method.
[0021] The invention also protects the use of titanium silicon molecular sieve TS-1 nanosheets in preparing a catalyst for the reaction of synthesizing cyclohexanone oxime by ammoxidation of cyclohexanone.
[0022] Preferably, cyclohexanone oxime is prepared according to the following steps: With 30wt% H2O2 as oxidant, water as solvent, tert-butanol as co-solvent and titanium silicalite TS-1 nanosheets as catalyst, cyclohexanone, solvent, co-solvent, 25wt% NH3·H2O, oxidant and catalyst are mixed, and the mixture is kept at 60℃~80℃ for 1h~3h. After the reaction is completed, the mixture is cooled to room temperature with an ice water bath to obtain cyclohexanone oxime.
[0023] Preferably, the molar ratio of the mass of titanium silicalite TS-1 nanosheets to cyclohexanone is 25 g to 32.5 g: 1 mol.
[0024] Preferably, the molar ratio of cyclohexanone: water: tert-butanol: NH3·H2O: H2O2 is 1:44-237:14-44:1.5-8:1-2.
[0025] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses tetrapropylammonium hydroxide, tetraethyl orthosilicate, tetrabutyl titanate and urea as raw materials, first crystallizes, then calcines, and prepares titanium silicon molecular sieve TS-1 nanosheets. Among them, tetrabutyl titanate is a titanium source, tetraethyl orthosilicate is a silicon source, and tetrapropylammonium hydroxide is a structure directing agent, which induces TS-1 to form an MFI structure, which is convenient for forming titanium silicon molecular sieve TS-1. Urea, as a cheap, easily available, green and pollution-free material, is one of the simplest organic compounds and is widely used in industrial and agricultural production; the present invention uses a urea-assisted synthesis method, and urea can spontaneously disperse on the surface of the crystal perpendicular to the b-axis, inhibiting the growth of the crystal along the b-axis. In addition, urea has the function of regulating the hydrolysis rate of tetraethyl orthosilicate and tetrabutyl titanate, and then forms a sheet of titanium silicon molecular sieve TS-1.
[0026] In addition, compared with the prior art, in the sheet-like titanium silicon molecular sieve TS-1 formed by the long-chain surfactant, since its structure is supported by the long-chain surfactant, the long-chain surfactant will decompose after calcination, and then collapse without support, but the pores will be blocked if the calcination operation is not performed. In the present invention, the crystal is not supported by urea because the growth is inhibited by urea, so even if calcined, the structure will not collapse.
[0027] 2. The present invention introduces urea into the preparation of titanium silicate TS-1 nanosheets, making the crystallization process easy to control. The removal of the template and urea will not affect the structure of the titanium silicate TS-1 nanosheets, and the titanium silicate TS-1 nanosheets do not contain anatase.
[0028] 3. The present invention introduces urea into the preparation of titanium silicalite TS-1 nanosheets. The introduction of urea does not affect the effective crystallization of Ti and its entry into the molecular sieve framework, and also has the function of regulating the hydrolysis rate of tetrabutyl titanate and tetraethyl orthosilicate, thereby preventing the formation of anatase that inhibits the catalytic effect of cyclohexanone ammoximation. Because the hydrolysis rates of tetrabutyl titanate and tetraethyl orthosilicate are different, the hydrolysis rate of titanium ester is fast and self-polymerization will occur to form anatase, while the Ti in anatase is not an active site and cannot react with H2O2 to produce Ti-OOH. Instead, it is easy to accelerate the ineffective decomposition of H2O2 and reduce the oxidation effect of H2O2.
[0029] 4. Under the condition of urea introduction, the synthesis of isopropanol-free titanium silicalite TS-1 nanosheets was also achieved, further reducing the synthesis cost.
[0030] 5. The titanium silicalite TS-1 nanosheets prepared by the urea-assisted synthesis method of the present invention have good diffusion performance in the preparation process of cyclohexanone oxime, that is, the reactants and products diffuse faster, and the active sites of the titanium silicalite TS-1 nanosheets are easily used for adsorption and desorption. The preparation process is simple, the cost is low, and it has high catalytic activity for the liquid phase cyclohexanone ammoximation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD pattern of the titanium silicon molecular sieve TS-1 nanosheets of Example 1.
[0032] Figure 2 This is the SEM image of the titanium silicalite TS-1 nanosheets of Example 1.
[0033] Figure 3 This is the XRD pattern of the titanium silicon molecular sieve TS-1 nanosheets of Example 2.
[0034] Figure 4 This is the SEM image of the titanium silicon molecular sieve TS-1 nanosheets of Example 2.
[0035] Figure 5 This is the XRD pattern of the titanium silicon molecular sieve TS-1 nanosheets of Example 3.
[0036] Figure 6 This is the SEM image of the titanium silicalite TS-1 nanosheets of Example 3.
[0037] Figure 7 This is the XRD diagram of the common titanium silicon molecular sieve TS-1 of comparative example 1.
[0038] Figure 8 This is the SEM image of the common titanium silicon molecular sieve TS-1 of Comparative Example 1. DETAILED DESCRIPTION
[0039] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0040] The present invention provides a method for preparing titanium silicon molecular sieve TS-1 nanosheets by using urea. Compared with the prior art hard template method for preparing mesoporous titanium silicon molecular sieve TS-1, since the hard template agent is insoluble in the solvent, the nucleation and growth mechanism does not conform to the traditional homogeneous nucleation and growth mechanism, and is generally heterogeneous nucleation, the nucleation and growth mechanism is more complicated, and the hard template is not easy to remove, and the crystal structure of titanium silicon molecular sieve TS-1 will be affected during the removal process. Compared with the soft template method for preparing mesoporous titanium silicon molecular sieve TS-1, urea is cheaper, more readily available, green and easy to remove than the soft template agent, so it will not affect the structure of titanium silicon molecular sieve TS-1 during the removal process; in addition, the urea of the present invention will not form a competitive relationship with the microporous structure directing agent tetrapropylammonium hydroxide during crystallization, and the crystal crystallization process is easier to control, and phase separation will not occur.
[0041] Compared with the preparation method of hollow titanium silicalite TS-1 in the prior art, urea is added during the synthesis of titanium silicalite TS-1 nanosheets without the need for secondary hydrothermal treatment. At the same time, the price of urea is much cheaper than tetrapropylammonium hydroxide, which effectively reduces the production cost.
[0042] The technical solution of the present invention is further explained by using embodiments and comparative examples, as shown below: Example 1 The preparation method of titanium silicate molecular sieve TS-1 nanosheets comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.01:0.25:23:0.5.
[0043] S2. Mix 20.336 g of 25 wt% tetrapropylammonium hydroxide solution and 26.148 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 3 g of urea to obtain a mixed solution.
[0044] 0.34 g of tetrabutyl titanate was added dropwise to 15.3 g of isopropyl alcohol while stirring to obtain a tetrabutyl titanate solution.
[0045] S3. Add tetrabutyl titanate solution to the mixed solution, then stir until clear, and then heat at 80°C to evaporate alcohol, where the alcohol includes isopropyl alcohol and alcohol in tetraethyl orthosilicate and tetrabutyl titanate, etc., and add water dropwise to keep the water amount constant to obtain a pretreatment solution.
[0046] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 72 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 6 hours to obtain titanium silicalite TS-1 nanosheets.
[0047] The XRD characterization results of the titanium silicon molecular sieve TS-1 nanosheets obtained in Example 1 are as follows: Figure 1 The SEM characterization results are shown in Figure 2 As shown in the figure, it can be seen that the MFI structure and crystallinity of the prepared titanium silicalite TS-1 nanosheet crystals have not changed, and the morphology is flaky.
[0048] The titanium silicon molecular sieve TS-1 nanosheets of Example 1 are used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0049] S2, in the reacted solution, add 6g ethanol and 0.15g diethylene glycol monoethyl ether, ethanol and diethylene glycol monoethyl ether are used for the amount of quantitative determination of pimelinketone and cyclohexanone oxime in gas phase, diethylene glycol monoethyl ether is internal standard, and ethanol is the solvent for dissolving diethylene glycol monoethyl ether, after stirring and mixing, remove catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal mark method and detect by gas chromatography, calculate the conversion rate of pimelinketone and the selectivity to cyclohexanone oxime according to the following formula: .
[0050] .
[0051] Wherein, C0 is the concentration of cyclohexanone before the reaction, C1 is the concentration of cyclohexanone after the reaction, and C2 is the concentration of cyclohexanone oxime generated.
[0052] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 94.8%, and the selectivity to cyclohexanone oxime was 100%.
[0053] Example 2 The preparation method of titanium silicalite TS-1 nanosheets is the same as the preparation steps of Example 1, except that the molar ratio of tetrapropylammonium hydroxide to tetraethyl orthosilicate is replaced from 0.25:1 to 0.3:1, and comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.01:0.3:23:0.5.
[0054] S2. Mix 24.403 g of 25 wt% tetrapropylammonium hydroxide solution and 26.148 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 3 g of urea to obtain a mixed solution.
[0055] 0.34 g of tetrabutyl titanate was added dropwise to 15.3 g of isopropyl alcohol while stirring to obtain a tetrabutyl titanate solution.
[0056] S3. Add the tetrabutyl titanate solution to the mixed solution, then stir until it is clear, heat at 80° C. to evaporate the alcohol, and add water dropwise to keep the water amount constant to obtain a pre-treated solution.
[0057] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 72 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 6 hours to obtain titanium silicalite TS-1 nanosheets.
[0058] The XRD characterization results of the titanium silicon molecular sieve TS-1 nanosheets obtained in Example 2 are as follows: Figure 3 The SEM characterization results are shown in Figure 4 As shown in the figure, it can be seen that the MFI structure and crystallinity of the prepared titanium silicalite TS-1 nanosheet crystals have not changed, and the morphology is flaky.
[0059] The titanium silicon molecular sieve TS-1 nanosheets of Example 2 are used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0060] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0061] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 97.3%, and the selectivity to cyclohexanone oxime was 100%.
[0062] Example 3 The preparation method of titanium silicalite TS-1 nanosheets is the same as the preparation steps of Example 1, except that tetrabutyl titanate is directly added dropwise to the mixed solution without adding isopropanol, and comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.01:0.25:23:0.5.
[0063] S2. Mix 20.336 g of 25 wt% tetrapropylammonium hydroxide solution and 26.148 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 3 g of urea to obtain a mixed solution.
[0064] S3. Add 0.34 g of tetrabutyl titanate dropwise to the mixed solution while stirring until the solution is clear, then heat at 80° C. to evaporate alcohol, and add water dropwise to keep the water amount constant to obtain a pretreatment solution.
[0065] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 72 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 6 hours to obtain titanium silicalite TS-1 nanosheets.
[0066] The XRD characterization results of the titanium silicon molecular sieve TS-1 nanosheets obtained in Example 3 are as follows: Figure 5 The SEM characterization results are shown in Figure 6 As shown in the figure, it can be seen that the MFI structure and crystallinity of the prepared titanium silicalite TS-1 nanosheet crystals have not changed, and the morphology is flaky.
[0067] The titanium silicon molecular sieve TS-1 nanosheets of Example 3 are used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80℃ and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0068] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0069] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 95.28%, and the selectivity to cyclohexanone oxime was 100%.
[0070] Example 4 The preparation method of titanium silicalite TS-1 nanosheets is the same as the preparation steps of Example 1, except that the molar ratio of tetrabutyl titanate to tetraethyl orthosilicate is replaced from 0.01:1 to 0.06:1, and comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.06:0.25:23:0.5.
[0071] S2. Mix 20.336 g of 25 wt% tetrapropylammonium hydroxide solution and 26.148 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 3 g of urea to obtain a mixed solution.
[0072] 0.34 g of tetrabutyl titanate was added dropwise to 15.3 g of isopropyl alcohol while stirring to obtain a tetrabutyl titanate solution.
[0073] S3. Add the tetrabutyl titanate solution to the mixed solution, then stir until it is clear, heat at 80° C. to evaporate the alcohol, and add water dropwise to keep the water amount constant to obtain a pre-treated solution.
[0074] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 72 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 6 hours to obtain titanium silicalite TS-1 nanosheets.
[0075] The titanium silicon molecular sieve TS-1 nanosheets of Example 4 are used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0076] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0077] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 57.34%, and the selectivity to cyclohexanone oxime was 98.87%.
[0078] Example 5 The preparation method of titanium silicalite TS-1 nanosheets is the same as the preparation steps of Example 1, except that the molar ratio of urea to tetraethyl orthosilicate is replaced from 0.5:1 to 0.66:1, the molar ratio of tetrapropylammonium hydroxide to tetraethyl orthosilicate is replaced from 0.25:1 to 0.35:1, the molar ratio of water to tetraethyl orthosilicate is replaced from 23:1 to 40:1, the amount of isopropanol is replaced from 15.3g to 17g, the crystallization time is increased from 72h to 80h, and the calcination time is increased from 6h to 7h, comprising the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.01:0.35:40:0.66.
[0079] S2. Mix 28.472 g of 25 wt% tetrapropylammonium hydroxide solution and 56.75 g of deionized water and stir for 30 min. Then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 4 g of urea to obtain a mixed solution.
[0080] 0.34 g of tetrabutyl titanate was added dropwise to 17 g of isopropyl alcohol while stirring to obtain a tetrabutyl titanate solution.
[0081] S3. Add the tetrabutyl titanate solution to the mixed solution, then stir until it is clear, heat at 80° C. to evaporate the alcohol, and add water dropwise to keep the water amount constant to obtain a pre-treated solution.
[0082] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 80 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 7 hours to obtain titanium silicalite TS-1 nanosheets.
[0083] The titanium silicon molecular sieve TS-1 nanosheet of Example 5 is used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0084] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0085] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 94.77%, and the selectivity for cyclohexanone oxime was 100%.
[0086] Example 6 The preparation method of titanium silicalite TS-1 nanosheets is the same as the preparation steps of Example 1, except that the molar ratio of tetrabutyl titanate to tetraethyl orthosilicate is replaced from 0.01:1 to 0.008:1, and tetrabutyl titanate is directly added dropwise to the mixed solution without adding isopropanol, the molar ratio of urea to tetraethyl orthosilicate is replaced from 0.5:1 to 0.3:1, the molar ratio of tetrapropylammonium hydroxide to tetraethyl orthosilicate is replaced from 0.25:1 to 0.125:1, the molar ratio of water to tetraethyl orthosilicate is replaced from 23:1 to 8:1, the crystallization temperature is replaced from 170°C to 110°C, the crystallization time is reduced from 72h to 24h, and the calcination time is reduced from 6h to 5h, comprising the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0.008:0.125:8:0.3.
[0087] S2. Mix 10.168 g of 25 wt% tetrapropylammonium hydroxide solution and 9.095 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 1.8 g of urea to obtain a mixed solution.
[0088] S3. Add 0.34 g of tetrabutyl titanate dropwise to the mixed solution while stirring until the solution is clear, then heat at 80° C. to evaporate alcohol, and add water dropwise to keep the water amount constant to obtain a pretreatment solution.
[0089] S4. Place the pretreated solution in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallize at 110°C for 24 hours, then wash with deionized water until the filtrate is neutral, dry at 60°C for 12 hours, and then calcine at 550°C for 5 hours to obtain titanium silicalite TS-1 nanosheets.
[0090] The titanium silicon molecular sieve TS-1 nanosheets of Example 6 are used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80℃ and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0091] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0092] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 68.42%, and the selectivity to cyclohexanone oxime was 100%.
[0093] Example 7 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the amount of the catalyst titanium silicon molecular sieve TS-1 nanosheet is replaced from 0.075 g to 0.125 g, and the reaction time is reduced from 3 h to 1 h, comprising the following steps: S1. Add 0.125g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 1h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0094] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the mixed solution after the reaction, stir and mix evenly, and remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0095] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 74.38%, and the selectivity to cyclohexanone oxime was 99.8%.
[0096] Example 8 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the amount of the catalyst titanium silicon molecular sieve TS-1 nanosheet is replaced from 0.075g to 0.05g, the amount of tert-butyl alcohol is replaced from 5.9g to 6.01g, the amount of water is replaced from 7.5g to 8.5g, the amount of NH3·H2O is replaced from 0.561g to 1.12g, the amount of H2O2 is replaced from 0.227g to 0.453g, and the reaction time is increased from 3h to 5h, comprising the following steps: S1. Add 0.05g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 8.5g water, 6.01g tert-butanol, 1.12g NH3·H2O and 0.453g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80℃ and keep it warm for 5h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0097] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0098] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 100%, and the selectivity to cyclohexanone oxime was 100%.
[0099] Example 9 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the amount of NH3·H2O is replaced by 0.561g to 0.2125g, and the amount of H2O2 is replaced by 0.227g to 0.26g, comprising the following steps: S1. Add 0.075g of catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g of cyclohexanone, 7.5g of water, 5.9g of tert-butanol, 0.2125g of NH3·H2O and 0.26g of H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0100] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0101] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 96.22%, and the selectivity to cyclohexanone oxime was 100%.
[0102] Example 10 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the amount of tert-butyl alcohol is replaced by 2 g from 5.9 g, the amount of water is replaced by 1.584 g from 7.5 g, the amount of NH3·H2O is replaced by 0.561 g to 0.182 g, the amount of H2O2 is replaced by 0.26 g from 0.227 g, and the reaction temperature is replaced by 60°C from 80°C, comprising the following steps: S1. Add 0.075g catalyst titanium silicon molecular sieve TS-1 nanosheets, 0.196g cyclohexanone, 1.584g water, 2g tert-butanol, 0.182g NH3·H2O and 0.26g H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 60°C and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0103] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0104] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 59.22%, and the selectivity to cyclohexanone oxime was 87.43%.
[0105] Comparative Example 1 The preparation method of ordinary titanium silicon molecular sieve TS-1 comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O of 1:0.01:0.3:23.
[0106] S2. Mix 24.403 g of 25 wt% tetrapropylammonium hydroxide solution and 26.148 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h to obtain a mixed solution.
[0107] 0.34 g of tetrabutyl titanate was added dropwise to 15.3 g of isopropyl alcohol while stirring to obtain a tetrabutyl titanate solution.
[0108] S3. Add the tetrabutyl titanate solution to the mixed solution, then stir until it is clear, heat at 80° C. to evaporate the alcohol, and add water dropwise to keep the water amount constant to obtain a pre-treated solution.
[0109] S4. Place the pretreated solution in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallize at 170°C for 72 hours, then wash with deionized water until the filtrate is neutral, dry at 60°C for 12 hours, and then calcine at 550°C for 6 hours to obtain ordinary titanium silicon molecular sieve TS-1.
[0110] The XRD characterization results of ordinary titanium silicon molecular sieve TS-1 are as follows Figure 7 The SEM characterization results are shown in Figure 8 As shown in the figure, it can be seen that the prepared ordinary titanium silicon molecular sieve TS-1 crystal MFI structure and crystallinity are good, and the morphology is spherical.
[0111] The common titanium silicon molecular sieve TS-1 of Comparative Example 1 is used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: S1. Add 0.075g of ordinary titanium silicon molecular sieve TS-1, 0.196g of cyclohexanone, 7.5g of water, 5.9g of tert-butanol, 0.561g of NH3·H2O and 0.227g of H2O2 into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. Heat the beaker to 80℃ and keep it warm for 3h. After the reaction is completed, cool it to room temperature with an ice-water bath to obtain cyclohexanone oxime.
[0112] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0113] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 87.1%, and the selectivity to cyclohexanone oxime was 100%.
[0114] Comparative Example 2 The preparation method of pure silicon molecular sieve TS-1 nanosheets comprises the following steps: S1. Weigh raw materials according to the molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide: H2O: urea of 1:0:0.125:8:0.5.
[0115] S2. Mix 10.168 g of 25 wt% tetrapropylammonium hydroxide solution and 9.095 g of deionized water and stir for 30 min, then add 20.833 g of tetraethyl orthosilicate and stir for 2 h. After the solution becomes clear, add 3 g of urea to obtain a mixed solution.
[0116] S3. Add 15.3 g of isopropanol to the mixed solution, then stir until it is clear, heat at 80° C. to evaporate the alcohol, and add water dropwise to keep the water amount constant to obtain a pretreatment solution.
[0117] S4. The pretreated solution was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, crystallized at 170°C for 72 hours, then washed with deionized water until the filtrate was neutral, dried at 60°C for 12 hours, and then calcined at 550°C for 6 hours to obtain pure silicon molecular sieve TS-1 nanosheets.
[0118] The pure silicon molecular sieve TS-1 nanosheets of Comparative Example 2 were used to carry out the ammoximation reaction of cyclohexanone, comprising the following steps: 0.075g of catalyst pure silicon molecular sieve TS-1 nanosheets, 0.196g of cyclohexanone, 7.5g of water, 5.9g of tert-butanol, 0.561g of NH3·H2O and 0.227g of H2O2 were added into a flask, with NH3·H2O being 25wt% and H2O2 being 30wt%. The mixture was heated to 80°C and kept warm for 3h. After the reaction was completed, the mixture was cooled to room temperature in an ice-water bath to obtain cyclohexanone oxime.
[0119] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0120] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 0%, and the selectivity to cyclohexanone oxime was 0%.
[0121] Comparative Example 3 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the catalyst titanium silicon molecular sieve TS-1 nanosheet is not used for catalysis, and the reaction time is 0 hours, and includes the following steps: 0.196g cyclohexanone, 7.5g water, 5.9g tert-butanol, 0.561g NH3·H2O and 0.227g H2O2 were added into a flask, with 25wt% NH3·H2O and 30wt% H2O2. The beaker was heated to 80℃ and kept warm for 0h, that is, cooled in an ice bath when the temperature reached 80℃. After the reaction was completed, it was cooled to room temperature in an ice-water bath to obtain cyclohexanone oxime.
[0122] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0123] Activity evaluation results: the conversion rate of cyclohexanone was 0%, and the selectivity to cyclohexanone oxime was 0%.
[0124] Comparative Example 4 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that NH3·H2O and H2O2 are not contained, and comprises the following steps: 0.075 g of catalyst titanium silicalite TS-1 nanosheets, 0.196 g of cyclohexanone, 7.5 g of water and 5.9 g of tert-butanol were added into a flask, and the beaker was heated to 60°C and kept warm for 5 hours. After the reaction was completed, it was cooled to room temperature with an ice water bath to obtain cyclohexanone oxime.
[0125] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0126] Activity evaluation results: the conversion rate of cyclohexanone was 0%, and the selectivity to cyclohexanone oxime was 0%.
[0127] Comparative Example 5 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the solvent H2O is not contained, and comprises the following steps: 0.075 g of catalyst titanium silicalite TS-1 nanosheets, 0.196 g of cyclohexanone, 5.9 g of tert-butanol, 0.561 g of NH3·H2O and 0.227 g of H2O2 were added into a flask, and the beaker was heated to 80°C and kept warm for 3 h. After the reaction was completed, it was cooled to room temperature with an ice water bath to obtain cyclohexanone oxime.
[0128] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0129] The activity evaluation results of the catalyst titanium silicalite molecular sieve TS-1 nanosheets: the conversion rate of cyclohexanone was 57.54%, and the selectivity for cyclohexanone oxime was 95.85%.
[0130] Comparative Example 6 The ammoximation reaction of cyclohexanone is the same as the preparation steps of Example 1, except that the auxiliary solvent tert-butyl alcohol is not contained, and comprises the following steps: 0.075 g of catalyst titanium silicalite TS-1 nanosheets, 0.196 g of cyclohexanone, 7.5 g of water, 0.561 g of NH3·H2O and 0.227 g of H2O2 were added into a flask, and the beaker was heated to 80°C and kept warm for 3 h. After the reaction was completed, it was cooled to room temperature with an ice water bath to obtain cyclohexanone oxime.
[0131] S2, add 6g ethanol and 0.15g diethylene glycol monoethyl ether to the solution after the reaction, stir and mix evenly, remove the catalyst by centrifugation. Take diethylene glycol monoethyl ether as internal standard, adopt internal standard method and detect by gas chromatography.
[0132] Catalyst activity evaluation results: the conversion rate of cyclohexanone was 100%, and the selectivity to cyclohexanone oxime was 39.68%.
[0133] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing titanium silicon molecular sieve TS-1 nanosheets, characterized in that: The steps include: The tetrapropylammonium hydroxide solution is mixed with water, and then tetraethyl orthosilicate is added and mixed evenly, and then urea is added to obtain a mixed solution; Tetrabutyl titanate is added dropwise to the mixed solution and stirred until it becomes clear to obtain a pre-treated solution; crystallizing the pretreated solution to obtain crystals; During the crystallization process, urea spontaneously disperses on the surface of the crystal perpendicular to the b-axis, inhibiting the growth of the crystal along the b-axis; The crystals are washed with water until neutral, and then calcined to obtain titanium silicon molecular sieve TS-1 nanosheets; Among them, the molar ratio of tetraethyl orthosilicate to urea is 1:0.3~0.
66.
2. The method for preparing titanium silicon molecular sieve TS-1 nanosheets according to claim 1, characterized in that: The molar ratio of tetraethyl orthosilicate: tetrabutyl titanate: tetrapropylammonium hydroxide is 1: 0.008~0.06: 0.125~0.
35.
3. The method for preparing titanium silicon molecular sieve TS-1 nanosheets according to claim 1, characterized in that: The crystallization method is: heating at 110°C~170°C for 24h~80h.
4. The method for preparing titanium silicon molecular sieve TS-1 nanosheets according to claim 1, characterized in that: The calcination conditions are: calcination at 550°C for 5h~7h.
5. The method for preparing titanium silicon molecular sieve TS-1 nanosheets according to claim 1, characterized in that: Tetrabutyl titanate can also be first dissolved in isopropanol to obtain a tetrabutyl titanate solution, and then the tetrabutyl titanate solution is added to the mixed solution.
6. A titanium silicon molecular sieve TS-1 nanosheet prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the titanium silicon molecular sieve TS-1 nanosheet as claimed in claim 6 in preparing a catalyst for the reaction of cyclohexanone ammoxidation to synthesize cyclohexanone oxime.
8. The use of the titanium silicon molecular sieve TS-1 nanosheet according to claim 7 in the preparation of a catalyst for the reaction of cyclohexanone ammoxidation to synthesize cyclohexanone oxime, characterized in that: Cyclohexanone oxime was prepared as follows: With 30wt% H2O2 as oxidant, water as solvent, tert-butanol as co-solvent and titanium silicalite TS-1 nanosheets as catalyst, cyclohexanone, solvent, co-solvent, 25wt% NH3·H2O, oxidant and catalyst are mixed, and the mixture is kept at 60℃~80℃ for 1h~3h. After the reaction is completed, the mixture is cooled to room temperature with an ice water bath to obtain cyclohexanone oxime.
9. The use of the titanium silicon molecular sieve TS-1 nanosheet according to claim 8 in preparing a catalyst for the reaction of cyclohexanone ammoxidation to synthesize cyclohexanone oxime, characterized in that: The molar ratio of the mass of titanium silicalite TS-1 nanosheets to cyclohexanone is 25g~32.5g:1mol.
10. The use of the titanium silicon molecular sieve TS-1 nanosheet according to claim 8 in preparing a catalyst for the reaction of cyclohexanone ammoxidation to synthesize cyclohexanone oxime, characterized in that: The molar ratio of cyclohexanone: water: tert-butanol: NH3·H2O: H2O2 is 1:44~237:14~44:1.5~8:1~2.
Citation Information
Patent Citations
Method for rapidly synthesizing TS-1 (Titanium Silicalite-1) molecular sieve by utilizing molecular-sieve hydrothermal-crystallization filter liquor
CN106629762A
Flaky TS-1 molecular sieve as well as preparation method and application thereof
CN116081635A
Synthesis method of nanoscale flaky TS-1 titanium silicalite molecular sieve
CN117401691A
Method for simply preparing hierarchical-pore titanium-rich TS-1 molecular sieve and application of hierarchical-pore titanium-rich TS-1 molecular sieve
CN118183774A
Method for preparing lamellar TS-1 molecular sieve by taking crystallization mother liquor as raw material
CN118771408A
Cited By
A thin-layer TS-1 nanosheet catalyst and a preparation method and application thereof
CN122665641A